Avant-Garde as Method: VKhUTEMAS and the Pedagogy of Space, 1920–1930 - Bokov, Anna (project baikal, 2021)
The book presents a new study on the Soviet Union's Higher Art and Technical Studios, known as Vkhutemas, and their pioneering curriculum that has been a source of inspiration for generations of architects, designers, and artists until the present day. The processes of institutionalizing the avant-garde, integrating architecture and science, teaching and praxis are analyzed. The experimental methodology of the pedagogical process is highlighted.
Keywords: Vkhutemas; architecture; pedagogy; avant-garde; praxis